PENGARUH KARAKTERISTIK PERUSAHAAN TERHADAP KEEFEKTIFAN SISTEM INFORMASI DITINJAU DARI DIMENSI KUALITAS PELAYANAN - S. Widanarto P (Jurnal Pendidikan Akuntansi Indonesia, 2004)
Pengaruh Karakteristik Perusahaan Terhadap Keefektifan Sistem Informasi Ditinjau dari Dimensi Kualitas PelayananMeasurement of information system effectiveness from service quality dimension has become an issue in MIS area. Researchers argue about the use of service quality (servqual) instrument to measure the information system effectiveness. Several studies indicate that service quality associates with company size and organization structure. This study intends to reexamine servqual instrument validity and reliability. Further more, this study attempts to measure information system effectiveness from service quality dimension and to investigate the impact of company size and organization structure on service quality. Item to total correlation, split-half method, and path analysis are used to test reliability of the instrument. Servqual instrument validity is tested by comparing servqual instrument items with in the framework of management information system theory. Wilcoxon test is used to test information system effectiveness by comparing the expected and perceived quality measurements. To measure the impact of company size and organization structure on service quality, a regression model is estimated. The data is collected with survey method. Questionnaire is sent to marketing managers, finance managers, human resources managers, and research and development managers as research subjects. The research is based on 82 valid responses. The result shows that, in general, servqual instrument is stastically reliable and valid as a measuring instrument. The result of information system effectiveness test from service quality dimension shows that there is a difference between manager’s perceived and expected service quality. Study result also shows that service quality is not influenced by company size and organization structure. Unlike previous studies, this study reinvestigates validity and reliability of the servqual instrument regardless of industry types and it attempts to investigate the impact of company size and organization structure on service quality. Key words :        servqual instrument, service quality, company size and organization structure